Effect of Deformation and Aging on Properties of Al-4.1%Cu-1.4%Mg Aluminum Alloy. (11th September 2013) - Wang, Hao; Li, Changsheng; Li, Jing; Wei, Xinglong; Mei, Ruibin
Abstract : Deformation scheme and preheat treatment of Al-4.1%Cu-1.4%Mg aluminum alloy are chosen, homogenizing annealing at 430°C for 1.5 h, cooling to 250°C in furnace at a cooling rate of less than 30°C/h and then cooling to room temperature to make Al-4.1%Cu-1.4%Mg aluminum alloy annealed fully. Heat treatment tests of Al-4.1%Cu-1.4%Mg aluminum alloy mainly consisting of rolling and aging were conducted, and the optimum peak of aging mechanism is 190°C/12 h. Through comparison of microstructure and mechanical properties with different deformation rates and aging mechanisms, effect of deformation rates and aging mechanism on properties of Al-4.1%Cu-1.4%Mg aluminum alloy was analyzed, and the optimum double peak of aging mechanism is 135°C/7 h + 185°C/14 h. Orthogonal experiments were carried out to analyze mechanical and electrical properties of tested materials before and after deformation, and the effect of aging mechanism on Al-4.1%Cu-1.4%Mg Al alloy was analyzed, and the optimum regression of aging mechanism is 190°C/12 h + 240°C/40 min + 190°C/12 h. Aging scheme is closely related to corrosion resistance of Al-4.1%Cu-1.4%Mg aluminum alloy, and three different aging schemes can improve the corrosion resistance. The exfoliation corrosion evaluation results show that the aging effect on exfoliation corrosion ability order is RRA > two-step aging > peak aging.